Grain Terminal Automation: A Case Study In The Control Of Control - Novek, Joel (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract In 1978 the Cargill grain export terminal in Thunder Bay, Ontario, underwent a modernization program which included the installation of a computerized process control system. The introduction of this technology challenged the prevailing division of labour in the grain industry under which a management supervisor issued commands by telephone and hourly workers responded by physically moving the grain through the terminal. Now, all grain movements are controlled by two operators sitting in front of VDT's in a control room. The question is: who shall control the control room? Management claimed this prerogative as an extension of the supervisor's role and in the initial automation plan both control room operators were to be supervisors. The union representing hourly employees saw this as a threat to its control over physical operations. A compromise was worked out under which management and the union would share control room duties. On each shift two control operators, one management, the other a member of the bargaining unit, work side by side before similar VDT's. A shop floor fiction, adhered to by both sides, maintains that the supervisor, by pressing certain buttons, is making "decisions" while the hourly employee, pressing other buttons, is merely carrying them out. This is an unstable compromise. Four years of negotiations and an arbitration hearing have failed to fully resolve the issue in this test case for grain industry automation.